2017
DOI: 10.1002/mus.25993
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the vagus nerves: Protocol, reference values, and side‐to‐side differences

Abstract: The right VN CSA is significantly larger than the left. These side- and age-specific reference values for the VN may be useful for future studies. Muscle Nerve 57: 766-771, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
100
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(133 citation statements)
references
References 26 publications
(59 reference statements)
23
100
6
2
Order By: Relevance
“…In diabetes, CSA has been reported to be decreased in the vagus nerve and increased in peripheral nerves . Present data confirm the recently reported right‐left differences in vagus nerve diameters . We additionally show that vagus nerve CSA is larger in women than in men.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In diabetes, CSA has been reported to be decreased in the vagus nerve and increased in peripheral nerves . Present data confirm the recently reported right‐left differences in vagus nerve diameters . We additionally show that vagus nerve CSA is larger in women than in men.…”
Section: Discussionsupporting
confidence: 91%
“…However, HR‐US systems are now available that provide online area measures as square millimeters with 1 or more (up to 3) digits after the decimal point, an option that can be chosen by the user in the system settings . The measures of vagus nerve CSA in the present study are lower than values reported earlier for a normal population . This can be explained by the more precise method applied here for calculating CSA.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Cross‐sectional area (CSA) is the most useful and reliable ultrasonographic parameter. Normal values of CSA of peripheral nerves were reported in several populations, but values obtained from different laboratories varied greatly . The normal size of a nerve may be different among different ethnic groups, as shown by Burg et al, who compared CSAs of the median nerve between samples of Indian and Dutch healthy populations .…”
Section: Introductionmentioning
confidence: 99%